Between Culture, Space, and Urban Identity: A Sustainable Cultural Approach for Revitalizing Dang Anom Park in Batam City - Nursyamsu, Lathifa; Venita Christine; Suwarlan, Stivani Ayuning (Journal of Civil Engineering and Planning (JCEP), 2025)
This study explores the revitalization of Dang Anom Park in Batam City through a sustainable cultural approach that integrates local identity, ecological sensitivity, and inclusive urban design. Rapid infrastructure-driven development in Batam has led to the neglect of public spaces, raising concerns over the loss of urban identity and diminished community interaction. The research aims to address this gap by developing a design strategy that reconnects cultural values with spatial functionality. Employing a qualitative descriptive method, the study includes literature review, field observations, and a SWOT analysis to assess the site’s conditions and potential. The proposed design is guided by three principles: sustainable nature, interactive public space, and accessibility for the elderly and disabled. Design interventions include strategic vegetation to mitigate pollution, cultural elements to enhance identity, and inclusive facilities to support diverse community engagement. The masterplan reimagines the park as an environmentally responsive and socially vibrant public space. The findings demonstrate that culturally grounded design can restore vitality to underused spaces while reinforcing urban identity. While the study offers a valuable conceptual framework, it is limited by its qualitative scope and single-site focus. Future research should incorporate community participation, implementation trials, and broader comparative studies across similar urban contexts. This research contributes to the discourse on sustainable urban development by offering a replicable model for culturally responsive park revitalization in rapidly urbanizing cities.